Cross-Country Stock Market Reactions to Major Terror Events: The Role of Risk Perception - Konstantinos Drakos (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
The extant literature has established that the occurrence of major terrorist events leads to negative abnormal returns not only to the location of the event, but also to third countries. However, the literature has neither investigated which are the diffusion mechanisms of terrorist shocks, nor whether the diffusion pattern is uniform. Given terrorism's idiosyncrasies and motivated by memory-based utility and the Availability heuristic, we conjecture that the stock market reaction depends on the country's perceived terrorism risk. We document that terrorism risk perception is able to explain a statistically significant portion of cross-country abnormal returns' variation. Moreover, risk perception's predictive power over abnormal returns is robust, even when we take into account countries' terrorism record or when we control for economic linkages.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: C33; D3; G14; G15; 330; Behavioral Economics; Risk Perception; Stock Market Return; Terrorism